Corpo-Voz em Contexto Coletivo: Ações Vocais Formativas no Canto Coral - Sousa, Simone Santos (2011)
Body and voice are together as an integral tool in the activity of singing. The goal of this work is to understand how this unique body is experienced in the teaching-learning singing. To this end, investigated the build process of the scenic-musical performances developed by Coral da Universidade Federal do Ceará. I used the ideas of Dalcroze and Orff concerning the inclusion of the body in the process of musical education, the experiences with the choir of Villa-Lobos and Marcos Leite, the ideas of the body to the actor proposed by Appia, Artaud and Grotowski, beyond the metaphors body suggested by Patricia Pederiva. I opted for the qualitative approach of ethnographic and descriptive, seeking to elucidate the meanings related to body-question voice in the choir of the UFC, hoping to get greater depth through qualitative methodology. To know the reality of the involved was used as an instrument of data collection interview, conducted with conductors, singers and group physical trainers, in addition to daily rehearsals and performances observed. Subsequently we analyzed the contents of the data collected. In analyzing the data collected, I came to a set of categories that can be summarized as follows: a) meanings of body, b) Difficulties found c) procedures and experiences. The analysis showed the importance of the work of preparing the body integrated vocal technique in the search for a unique body, integral and organic, in which body, voice and movement to integrate more freely